1999
DOI: 10.1128/jvi.73.10.8457-8468.1999
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of the Role of Herpes Simplex Virus Type 1 Glycoprotein K in Infectious Virus Production and Egress

Abstract: Herpes simplex virus type 1 (KOS)ΔgK is a mutant virus which lacks glycoprotein K (gK) and exhibits defects in virion egress (S. Jayachandra, A. Baghian, and K. G. Kousoulas, J. Virol. 69:5401–5413, 1997). To further understand the role of gK in virus egress, we constructed recombinant viruses, ΔgKhpd-1, -2, -3, and -4, that specified gK amino-terminal portions of 139, 239, 268, and 326 amino acids, respectively, corresponding to truncations immediately after each of the four putative membrane-spanning domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(30 citation statements)
references
References 48 publications
0
29
1
Order By: Relevance
“…HSV-1 carries at least 85 genes, which are divided into two groups based on whether they are essential for virus replication in vitro (28). Both the gK and UL20 genes are considered essential genes for HSV-1 replication in vitro and in vivo (2)(3)(4)(29)(30)(31)(32). We have reported previously that immunization of mice with HSV-1 gK exacerbates eye disease in ocularly infected mice (33,34) and that recombinant viruses expressing two additional copies of HSV-1 gK exacerbate eye disease in ocularly infected mice (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HSV-1 carries at least 85 genes, which are divided into two groups based on whether they are essential for virus replication in vitro (28). Both the gK and UL20 genes are considered essential genes for HSV-1 replication in vitro and in vivo (2)(3)(4)(29)(30)(31)(32). We have reported previously that immunization of mice with HSV-1 gK exacerbates eye disease in ocularly infected mice (33,34) and that recombinant viruses expressing two additional copies of HSV-1 gK exacerbate eye disease in ocularly infected mice (25).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the roles of UL20 and its regulation in vivo are hampered by the essential role of UL20 and the inability of UL20 deletion mutants of HSV-1 to replicate efficiently in vitro or in vivo (3,4,32). Our recent construction of GODZ Ϫ/Ϫ mice (19), however, enabled investigation of the contribution of the GODZ component of the UL20-gK network to HSV-1 infectivity using MEFs derived from these mice, as well as in vivo analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas HSV-1 gK had so far only been detected in the endoplasmic reticulum and nuclear membranes of infected cells (14), it has been found in virions of PrV and VZV (25,32). Detailed studies of HSV-1, PrV, and VZV demonstrated an important role for gK in virus replication (8,15,25,32). Only small plaques or foci of infected cells were observed after infection of noncomplementing cells with gK mutants of HSV-1 and PrV (14,25), and productive viral replication was prevented by deletion of VZV gK (32).…”
mentioning
confidence: 99%
“…Based on the model of gK topology (31), different functional domains for gK involved in nucleocapsid envelopment, membrane fusion, virus replication, and egress have been proposed (8). Effects on virus yield, plaque formation, and virus envelopment were tentatively assigned to amino-terminal portions of gK, comprising the N terminus, a cytoplasmic loop, and the second extracellular domain.…”
mentioning
confidence: 99%